Penguatan Pendekatan Filosofis dalam Metodologi Studi Islam - Taufik Ramdhani; Desta Rafi Bagus Pratama; Maftuh Ajmain (PT. Saha Kreasi Indonesia, 2026)
The philosophical approach in Islamic studies is a methodological framework that emphasizes the role of reason in understanding Islamic teachings logically, critically, and reflectively. This article aims to elaborate on the basic concepts of the philosophical approach, explain its application across various Islamic disciplines, and identify the figures who have contributed to its development. This research employs a qualitative method with a library research approach. The findings indicate that the philosophical approach is capable of connecting revelation and reason proportionally, thereby producing an understanding of Islam that is not only normative but also contextual and relevant to contemporary developments. Furthermore, this approach encourages the emergence of a more open, moderate, and dialogical religious attitude.